The Effect of Moringa Leaf Processing on Hemoglobin Levels in Stunted Toddlers - Sahureka, Marthina; Fauziah, Munaya; Sutini, Titin; Purwati, Nyimas Heny; Nuraidah, Nuraidah (Indonesian Journal of Global Health Research, 2024)
Children facing prolonged malnutrition are susceptible to stunting, a condition marked by insufficient hemoglobin levels crucial for oxygen and nutrient transportation in the bloodstream. Addressing this issue involves dietary interventions rich in protein and iron, such as processed Moringa leaves. This study aims to identify the effect of giving processed Moringa leaves on increasing hemoglobin levels in stunted toddlers in the Tawiri Community Health Center working area, Ambon City. This research method is a quasi-experimental two-group pretest-posttest design with control group with a sample of 22 toddlers in each group. The data in this study were collected using the Morisky Medication Adherence Scale-8 (MMAS), a measurement tool for medication adherence in patients with chronic diseases, consisting of 8 questionnaire items. The classification of the results is as follows: a score of <6 indicates low adherence, 6-7 indicates medium adherence, and 8 indicates high adherence. The research results showed that the average hemoglobin level in the intervention group before and after administering processed Moringa leaves was 10.20-11.34 (difference: 1.14 g/dl), while in the control group it was 10.42 g/dl-10.45 g/dl (difference: 0.03 g/ dl). Based on the results of the analysis, it was found that the p-value was 0.001, which meant that there was a difference in the increase in hemoglobin levels of stunted toddlers in the intervention group and the control group. In the multivariate analysis of the confounding variables (age, gender, nutritional adequacy, and physical activity) that influenced hemoglobin levels were comorbidities with a p-value of 0.012. The results of this research can be used as a basis for parents to give processed Moringa leaves to stunting toddlers as an effort to increase hemoglobin levels.